The Impact of Poor Health and Nutrition on Education in Kenya - Ngao , Gladys Kasiva; Musyoka-Kamere, Isabella M. (African Journal of Education,Science and Technology (AJEST), 2013)
Poor health and nutrition prevent children from attending school and effectively participating in learning. This is why the UNESCO, UNICEF, WHO and the World Bank to launch the Focus Resources on Effective School Health (FRESH) during the School health and Nutrition Framework at the World Education Forum in Dakar in 2000 as an effort to mainstream school health and nutrition in education sector programmes. Notably, learners’ nutritional status and educational performance are strongly related. As a result, enhanced health leads to higher educational achievement and healthier students who learn new skills and competencies more efficiently, and invest more in schooling. Consequently, well-nourished students miss fewer days of school due to illness, while the malnourished ones are not as productive. Chronic malnutrition inhibits growth, retards mental development and reduces motivation and energy levels, resulting to a reduced educational attainment and delay in school entry. School health and nutrition programmes contribute not only to health outcomes, but to improved access to and completion of education as well. The goal of universal education cannot be achieved while the health needs of learners remain unmet; therefore, a core group of cost-effective activities must be implemented for learners in all schools towards meeting their needs and to deliver on the promise of Education for All (EFA). This paper assesses the basic facts about health and nutrition and its impact on primary education in Kenya. It will also explore problems and issues in health, nutrition and education, and suggest possible solutions.